2009
DOI: 10.1309/ajcp1gyi7ehqyuyk
|View full text |Cite
|
Sign up to set email alerts
|

Flow Cytometric Immunophenotyping and Minimal Residual Disease Analysis in Multiple Myeloma

Abstract: Presence of normal plasma cells (PCs), hemodilution of bone marrow aspirate, and changes in the immunophenotype are important considerations in minimal residual disease (MRD) assessment in multiple myeloma (MM). We evaluated 124 subjects-107 with MM, 11 with Hodgkin lymphoma, and 6 allogeneic stem cell transplantation donors-for the immunophenotype of neoplastic, reactive, and normal PCs respectively. Of the patients with MM, 36 were evaluated for MRD and 23 for a change in immunophenotype after chemotherapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 18 publications
0
29
0
Order By: Relevance
“…A BD FACSAria flow cytometer (Becton, Dickinson and Company, Franklin Lakes, NJ, USA) was used to isolate the MM cells and PCs. For FACS, MM cells were gated in the CD38 bright / CD45 low-dim /CD19 − /CD56 low-high or CD38 bright /CD45 lowdim /CD19 + /CD56 + area, and NPCs were gated in the CD38 bright /CD138 bright area [15,16]. Isolated cells were stained with May-Grünwald-Giemsa cytochemical staining solution (Sigma-Aldrich, St. Louis, MO, USA); each plasma cell was confirmed morphologically as previously described [17].…”
Section: Flow Cytometrymentioning
confidence: 99%
“…A BD FACSAria flow cytometer (Becton, Dickinson and Company, Franklin Lakes, NJ, USA) was used to isolate the MM cells and PCs. For FACS, MM cells were gated in the CD38 bright / CD45 low-dim /CD19 − /CD56 low-high or CD38 bright /CD45 lowdim /CD19 + /CD56 + area, and NPCs were gated in the CD38 bright /CD138 bright area [15,16]. Isolated cells were stained with May-Grünwald-Giemsa cytochemical staining solution (Sigma-Aldrich, St. Louis, MO, USA); each plasma cell was confirmed morphologically as previously described [17].…”
Section: Flow Cytometrymentioning
confidence: 99%
“…Analysis of the number of neoplastic plasma cells as a percentage of total plasma cell count rather than as a percentage of total leukocyte count is therefore recommended since hemodilution would likely cause a proportionate reduction in the numbers of both the normal and the clonal plasma cells [14]. A study by Gupta et al has shown that a neoplastic plasma cell index (percentage of neoplastic/non-neoplastic plasma cells) of less than 30 on flow cytometry might further be of potential use in differentiating complete treatment response (immunofixation negative) from a partial re sponse (immunofixation positive) [14]. The second challenge in assessing MRD by flow cytometry is "antigen shifts" in neoplastic cells following treatment [15].…”
Section: Utility In Monitoring Residual Diseasementioning
confidence: 99%
“…Even though only 70-80% of the MM is CD56-positive, they could show that immunostain-ing with CD56 detected three positive samples that were not recognized by morphology or light chain restriction out of 53 negative biopsies. Gupta et al [77] addressed the same question using flow cytometric phenotyping in 107 patients. The immunophenotype of normal and reactive PCs was similar and differed from that of neoplastic PCs with respect to CD19, CD45, CD56, CD52, CD20, and CD117.…”
Section: Ancilliary Techniquesmentioning
confidence: 99%